Group Differences in Student Performance in the Selection to Higher Education: Tests vs Grades - Wikström, Christina; Wikström, Magnus (Frontiers in Education, 2017)
Student selection in the Swedish admission to higher education system is based on two fundamentally different performance measures: their criterion-referenced upper secondary grade point average (GPA) or their score on a norm-referenced and multiple-choice admissions test (SweSAT). Several student characteristics are known to affect rankings in such assessments. The objectives of this study are to assess main and interactive effects of several variables that influence rankings obtained from these measures in greater detail than previously attempted, and assess the findings from a fairness perspective. The data consist of test scores, upper secondary grades and background information for SweSAT participants, aged 19 to 25 years, who took the test in the autumn of 2011 (N=23,214) or spring of 2012 (N= 27,075). The data were analysed through correlation and regression analysis. The results support previous findings that gender, parents’ education, and immigration status are all influential. Males obtain better SweSAT scores than females while females obtain better GPAs, in accordance with previous findings regarding gender-related variations in rankings provided by similar instruments. Moreover, we found the same pattern in scores for specific components of the test and grades in specific subjects, suggesting that the test and GPA measure different, gender-related, things. In addition, students with an immigrant background seem to be more highly ranked by grades than by the SweSAT, largely due to differences in assessments of their verbal skills. □